Groundwater recharge estimation from modified soil moisture balance approach at the University Of Ibadan, lbadan, Nigeria. (2006)
Amount of water that may be extracted from an aquifer without depletion is primarily dependent on recharge. Thus, a quantitative evaluation of spatial and temporal groundwater recharge distribution is a pre-requisite for operating groundwater resource system in an optimal manner. A step-by step procedure of National Resources Conservation Services (NRCS) was used to estimate groundwater recharge based upon modified soil moisture balance approach at the University of Ibadan which covers about 1032 hectares of land. The methodology incorporates the theory of NRCS method of finding storage index. Water recharges were highest in sandy clay loam (59.0% Sand, 11.4% Silt, 29.6% Clay) between 113.1-122.5cm/hr, followed by sandy clay (58.1% sand, 8.9% silt, 33.0% clay) with values between 41.6- 55.3cm/hr and sandy clay (56.8% sand, 7.5% silt, 35.7% clay) between 38.4-47.9cm/hr. This methodology gives better estimates of groundwater recharge because it takes into consideration climatic data, land use pattern and soil properties of study location. However, conventional methods of precipitation minus evapotranspiration minus runoff, is subjective to measurement errors and the method of calculating groundwater recharge by multiplying a constant specific yield value by the water table rise over a certain time interval may also be erroneous, especially in shallow aquifers.